PENGARUH BUDAYA UNIVERSITAS TERHADAP PERFORMA UNIVERSITAS MELALUI ORIENTASI KEWIRAUSAHAAN DAN PEMBERDAYAAN SEBAGAI VARIABEL INTERVENING - Utomo, Suhardi (Business Accounting Review, 2015)
This study aimed to examine the affect of university culture on the university performance with entrepreneurial orientation and empowerment asÂ intervening variable. The samples and data used in this study were obtained from 420 students in six private universities in Surabaya by using questionnaire. The sample selection was done by using purposive sampling. The method of data processing was done by using descriptive analysis and partial least square method (PLS).The result showed a significant and positive impact of university culture to university performance. Entrepreneurial orientation and empowerment cannot become intervening variables, but may help to explain the impact of university culture on university performance. University culture had a positive and significant impact on entrepreneurial orientation and empowerment. Entrepreneurial orientation and empowerment were later proved to have positive and significant impact on the university performance